Ionizing radiation-engineered nanogels as insulin nanocarriers for the development of a new strategy for the treatment of Alzheimer's disease. (February 2016) - Picone, Pasquale; Ditta, Lorena Anna; Sabatino, Maria Antonietta; Militello, Valeria; San Biagio, Pier Luigi; Di Giacinto, Maria Laura; Cristaldi, Laura; Nuzzo, Domenico; Dispenza, Clelia; Giacomazza, Daniela; Di Carlo, Marta
Abstract: A growing body of evidence shows the protective role of insulin in Alzheimer's disease (AD). A nanogel system (NG) to deliver insulin to the brain, as a tool for the development of a new therapy for Alzheimer's Disease (AD), is designed and synthetized. A carboxyl-functionalized poly(N-vinyl pyrrolidone) nanogel system produced by ionizing radiation is chosen as substrate for the covalent attachment of insulin or fluorescent molecules relevant for its characterization. Biocompatibility and hemocompatibility of the naked carrier is demonstrated. The insulin conjugated to the NG (NG-In) is protected by protease degradation and able to bind to insulin receptor (IR), as demonstrated by immunofluorescence measurements showing colocalization of NG-In FITC with IR. Moreover, after binding to the receptor, NG-In is able to trigger insulin signaling via AKT activation. Neuroprotection of NG-In against dysfunction induced by amyloid β (Aβ), a peptide mainly involved in AD, is verified. Finally, the potential of NG-In to be efficiently transported across the Blood Brain Barrier (BBB) is demonstrated. All together these results indicate that the synthesized NG-In is a suitable vehicle system for insulin deliver in biomedicine and a very promising tool to develop new therapies for neurodegenerative diseases.